Contact and Non-Contact Measurements of Chlorophyll-a in Water Based on Laser Spectroscopy - Xiuyue Dong; Xiaohua Che; Zhaoshuo Tian (Journal of Marine Science and Engineering)
Chlorophyll-a fluorescence detection is an important technique for monitoring water quality. In this paper, we proposed an approach that employs the ratio of fluorescence to Raman obtained from contact and non-contact laser-induced fluorescence detection methods as the key for the detection of Chlorophyll-a in water. At first, extracted Chlorophyll-a solutions were prepared, and each sample was tested using two detection methods. The true values of the samples were measured in the laboratory using spectrophotometry. Then, the detection system was calibrated through the linear fitting of Chlorophyll-a and the fluorescence–Raman ratio. The linear correlation coefficients of contact and non-contact detection were 0.9453 and 0.9401, respectively. Finally, we tested the actual water samples in two ways, and compared the test results with the value measured using the national standard method. The root mean square error (RMSE) of contact and non-contact detection was 0.16 and 0.23, respectively. The results show that the two detection methods have high accuracy and sensitivity, and preliminary preparation of samples is not required. Compared with contact detection, the non-contact detection results had higher accuracy and stronger anti-interference, but the maintenance cost was higher because the probe is vulnerable to wear. The advantage of non-contact detection is that it avoids sample contamination and is easy to apply over large areas of water. In the future, it can be used for the real-time monitoring of algal biomass in water by selecting the appropriate detection method according to the requirements of the application.